The effect of Nigella Sativa syrup on the relief of cyclic mastalgia: A triple-blind randomized clinical trial - Seyedeh Tahereh Mirmolaei; Asiie Olfatbakhsh; Hasan Falah Huseini; Ehsan Kazemnezhad Leyli; Ameneh Sotoodeh Moridiani (Tehran University of Medical Sciences, 2017)
Background & Aim: Mastalgia is one of the most common complaints of women and its cyclic type constitutes two-thirds of the cases. This study aimed to determine the effect of Nigella Sativa syrup on cyclic mastalgia. Methods & Materials: This study is a triple-blind randomized clinical trial (IRCT201104304785N3). The study samples included 65 women with cyclic mastalgia referred to the Breast Cancer Research Center (BCRC), Academic Center for Education, Culture and Research (ACECR) in Tehran in 2014-2015. The samples were randomly divided into two groups: intervention group (Nigella Sativa=36) and placebo group (oral paraffin=36). The pain was measured by the VAS and McGill Short Form questionnaire two months before and three months after the intervention. Data were analyzed using statistical tests on the SPSS software version 18. Results: The results of the VAS and McGill pain score changes showed a significant difference between the two groups. Considering that the interaction between time and group was significant, the two groups were compared at each stage using independent t-test and the Bonferroni correction test. Thus, there was no significant difference between the two groups of Nigella Sativa and placebo on the basis of the McGill instrument but a significant difference was observed between the two groups on the basis of the VAS (P=0.002). Conclusion: According to the results, Nigella Sativa reduces pain more than placebo. Therefore, it can be used along with other medications for the treatment of mastalgia.